2014
DOI: 10.1002/mrm.25282
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated 4D quantitative single point EPR imaging using model‐based reconstruction

Abstract: Purpose EPRI has surfaced as a promising non-invasive imaging modality that is capable of imaging tissue oxygenation. Due to extremely short spin-spin relaxation time, EPRI benefits from single point imaging and inherently suffers from limited spatial and temporal resolution, preventing localization of small hypoxic tissues and differentiation of hypoxia dynamics, making accelerated imaging a crucial issue. Method In this study, methods for accelerated single point imaging were developed by combining a bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, by slightly oversampling the SPI region (Nyquist sampling requires approximately 300 SPI encodings, whereas 925 were used in this study), which requires an additional scan time of only 2.5 s, it was possible to obtain multiple UTE images. With the ability to obtain multiple UTE echoes, it may be possible to improve the reconstruction further, using model‐constrained approaches or directly estimating the normalT2* of bone by additional SPI oversampling to secure a wider range of TEs, which could be used to assign continuous HU values based on the normalT2* of bone or contrast of PDW UTE image . In this study, we have shown the efficacy of using multiple UTE images to improve air and bone detection.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, by slightly oversampling the SPI region (Nyquist sampling requires approximately 300 SPI encodings, whereas 925 were used in this study), which requires an additional scan time of only 2.5 s, it was possible to obtain multiple UTE images. With the ability to obtain multiple UTE echoes, it may be possible to improve the reconstruction further, using model‐constrained approaches or directly estimating the normalT2* of bone by additional SPI oversampling to secure a wider range of TEs, which could be used to assign continuous HU values based on the normalT2* of bone or contrast of PDW UTE image . In this study, we have shown the efficacy of using multiple UTE images to improve air and bone detection.…”
Section: Discussionmentioning
confidence: 86%
“…Restricting the effective FOV would be a simple strategy to accelerate CSPI, for instance, by using coils with small volume and sensitivity (e.g., surface coils) or applying slab selection, for example, by using a half pulse or Shinnar–Le Roux pulse with minimum phase . Furthermore, a 3D non‐Cartesian sampling pattern with variable density can be used to produce noise‐like aliasing patterns that can be removed by postprocessing, such as denoising or compressed sensing techniques . With any of the above strategies for accelerating CSPI, the key advantageous feature of CSPI, true phase imaging, will be still preserved.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Furthermore, a 3D non-Cartesian sampling pattern with variable density can be used to produce noise-like aliasing patterns that can be removed by postprocessing, such as denoising or compressed sensing techniques. 33,34 With any of the above strategies for accelerating CSPI, the key advantageous feature of CSPI, true phase imaging, will be still preserved. In future studies, we will explore the aforementioned strategies more rigorously to evaluate CSPI in clinical applications, including patients with metallic implants or hemophilia.…”
Section: F I G U R E 3 Reconstructed Images For Iron Phantom Qsm (A)mentioning
confidence: 99%
“…Moreover, hybrid encoding schemes with an oversampled SPI encoded region may allow reconstruction of images at multiple TEs in early encoding times, which can be used to estimate short T 2 * parameters with a single experiment (e.g., using k‐space extrapolation methods as recently proposed in single point electron paramagnetic resonance imaging) . The additional scanning time imposed by oversampling SPI encoded region can be reduced by using variable density sampling pattern and appropriate reconstruction method such as compressed sensing using k‐space domain data or model‐based reconstruction using k‐space domain data and free induction decay data (parameter domain) simultaneously .…”
Section: Discussionmentioning
confidence: 99%